TEKNOLOGI INFORMASI MEMODERASI PENGETAHUAN PERPAJAKAN DAN TINGKAT KEPERCAYAAN PADA PEMERINTAH TERHADAP KEPATUHAN WAJIB PAJAK PBB-P2 - Mentu, Fabiola Fernandes; Ngadiman (Jurnal Kontemporer Akuntansi, 2025)
The purpose of this research is to determine the effect of Information Technology in moderating Taxation Understanding, Tax Penalty Strictness, and Level of Trust in the Government on the Compliance of PBB-P2 Taxpayers in Tomohon Barat District, Tomohon City. This study is specifically focused on all PBB-P2 taxpayers within the scope of Tomohon Barat District, Tomohon City. The researcher chose Tomohon Barat because it is the best district in Tomohon City in terms of paying PBB-P2 taxes. The method used in this research is purposive sampling with 300 respondents obtained through questionnaires distributed to 313 respondents, analyzed using Smart PLS 4. The research method employed in this study is a quantitative method using primary data through observation of events, people, objects, and by distributing questionnaires to individuals. The results of the study indicate that there is no effect of Taxation Understanding and Tax Penalty Strictness on Taxpayer Compliance, but there is an effect of the Level of Trust in the Government on Taxpayer Compliance. The moderation of Information Technology on Taxation Understanding, Tax Penalty Strictness, and Level of Trust in the Government shows an effect on Taxpayer Compliance.